An Ethnographic Analysis Of The Religious And Mystical Healing Functions Of Traditional Household Objects Of Khorezm - Matchanova Sanobar Mukhamedjanovna (Genius Journals, 2025)
This article examines the religious-mystical healing practices associated with household items in the Khorezm region. Earthenware and glass vessels inscribed with Qur’anic verses, combined with colors and materials, were used to treat illnesses, protect against spirits, and strengthen spiritual well-being.
Keywords: Religious-mystical; healing; earthenware